Construction of 3D clay thickness models of Turku for urban planning and infrastructure - Anttila, Noora (My University, 2023)
The southern and western parts of Finland have been mostly submerged during the different phases of development of the Baltic Sea Basin. For this reason, these areas have experienced saline and brackish water phases, which has affected the sedimentation settings. Based on the previous studies of Baltic Sea and its deposition environments in onshore areas, the conditions and the seabed topography have a major role in the deposition of fine-grained sediments and their properties. Areas of fine-grained sediments challenges the community engineers, as the population in cities are growing and the urban expansion requires more unfavorable areas for land use. Especially in coastal cities like Turku, the fine-grained deposits create challenging conditions for construction. This study provides a characterization of fine-grained sedimental deposits in the Turku area by producing three-dimensional geological models for urban planning and construction. Paleotopographic models for the ancient Baltic Sea Basin in the Turku area i) after deglaciation and ii) during the Litorina transgression were built and classified into bathymetric zones and structures. Combining the topographic classifications with the thickness of fine-grained sediments,it was possible to produce a demonstration of the characteristics of sedimentary environments in the Turku area. Nearly 60% of the research area contains fine-grained sediments, where the thickest deposits are mainly located in depressions and joint valleys along the Aurajoki river and around the harbor area. Except for the biggest joint valleys, the topography of fine-grained sediments in the area has very small features with lots of smaller depressions, hills, and slopes. In addition, this study sidelines the possibility to predict and model potential areas that contain acid sulphate soils with characterization of fine-grained sediments. This study increases knowledge about Turku areas surficial deposits and can be used as a support for construction and urban planning in the Turku region or as a spatial information model guide on the presence and composition of building foundations. The methodology used in this study can be utilized in similar areas on the coasts of Baltic Sea to study fine-grained sediments.

Suomen etelä- ja länsiosat ovat olleet enimmäkseen veden alla Itämeren altaan eri kehitysvaiheissa. Tästä syystä erityisesti Suomen rannikkoalueilla on koettu suolaisia ja murtovesivaiheita, jotka ovat vaikuttaneet sedimentaatio-olosuhteisiin. Aiemmat tutkimukset Itämeren ja sen rannikkoalueiden laskeumaympäristöistä kertovat, että merenpohjan pinnanmuodot ja olosuhteet ovat keskeisessä asemassa hienorakeisten maalajien sedimentoitumisessa ja niiden ominaisuuksissa. Hienorakeiset sedimentit kaupunkien alueilla haastavat yhdyskuntatekniikkaa, kun väkiluvun kasvamisen myötä kaupunkeja joudutaan laajentamaan maankäytön kannalta epäsuotuisille alueille. Erityisesti Turun kaltaisissa rannikkokaupungeissa saviset kerrostumat luovat haastavat olosuhteet rakentamiselle. Tässä tutkimuksessa esitetään Turun alueen savikoiden esiintymisalueet ja niiden paksuudet, tuottamalla kaupunkisuunnittelua ja -rakentamista palvelevia kolmiulotteisia geologisia malleja. Luomalla alueesta muinaisen Itämeren altaan paleotopografiset mallit i) jääkauden jälkeen sekä ii) Litorinameren aikana, voitiin alue luokitella yksityiskohtaisesti topografisten ominaisuuksien mukaisesti. Yhdistämällä topografiset luokitukset savenpaksuus-malliin pystyttiin laatimaan havainnollistava malli Turun alueen sedimenttikerrostumista. Lähes 60 % tutkimusalueesta sisältää hienorakeisia sedimenttejä, joista paksuimmat kerrostumat sijaitsevat pääasiassa murroslaaksoissa Aurajoen varrella sekä satama-alueella. Lukuun ottamatta suurimpia murroslaaksoja, alueen savisedimentit ovat topografialtaan hyvin pienipiirteisiä, sisältäen paljon pieniä painanteita, kohoumia ja rinteitä. Lisäksi tässä tutkimuksessa on tarkasteltu edellytyksiä mallintaa potentiaalisia happamien sulfaattimaiden alueita havainnollistettujen savikerrosten perusteella. Tämän tutkimuksen tuloksia voidaan hyödyntää Turun alueen rakennushankkeiden ja aluesuunnittelun tukena sekä suuntaa antavana paikkatietomallina rakennuspohjan esiintymisestä ja koostumuksesta. Tutkimuksessa käytettyjä menetelmiä voidaan soveltaa vastaavanlaisille hienorakeisten sedimenttien alueilla tehtäville samanlaisille tutkimuksille Itämeren rannikoilla.
Keywords: Paleotopographic classification, fine-graines sediments, depositional environments, Benthic Terrain Modeler (BTM), land use, Turku, Paleotopografinen luokittelu, hienorakeiset sedimentit, kerrostumisympäristöt, Benthic Terrain Modeler (BTM), maankäyttö, Turku